(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدراسة إلى تحديد دور مواقع التواصل الاجتماعي في توفير المعلومات للمستهلكين عند قيامهم بعملية الشراء. حيث أصبحت مواقع وشبكات التواصل الاجتماعي اليوم وسيلة في متناول مختلف فئات المجتمع، وتميزت هذه المواقع بتوافرها والتصاقها الدائم بالمستهلكين. لذلك وجدت شركات الأعمال أن هذه المواقع تعد وسط جيد للوصول إلى عملائها من خلال استخدامها كأداة في الترويج لمنتجاتها، وهذا ما شجع المستهلكين على استخدام هذه المواقع في سبيل الحصول على المعلومات المتوفرة عبرها واتخاذ قرار الشراء المناسب. وقد تمت هذه الدراسة من خلال توزيع استبانة على عينة ميسرة من مستهلكي الألبسة الجاهزة في الساحل السوري، وبلغ عدد هذه الاستبانات 84 استبانة، تم من خلالها الحصول على البيانات المطلوبة. كما تم الاستعانة ببرنامج spss25 الإحصائي لتحليل البيانات والحصول على النتائج. ومن بين النتائج التي تم الحصول عليها أن أكثر مواقع التواصل الاجتماعي التي تستخدم في البحث عن المعلومات هو موقع فيس بوك وأقلها هو تويتر. كما أن المستوى التعليمي للمستهلكين يلعب دوراً كبيراً في البحث عن المعلومات عبر هذه المواقع. بالإضافة إلى ذلك توصلت إلى أنه كلما زاد عمر المستهلك كلما زاد بحثه عن المعلومات التي يرغب بها وتساعده في اتخاذ قرار الشراء المناسب. لذلك من الضروري أن تتوجه شركات الأعمال إلى استثمار كافة مواقع التواصل الاجتماعي المتوفرة لدى المستهلكين في الترويج لأعمالها وتقديم المعلومات الكافية التي يحتاجها المستهلكين. بالإضافة إلى وضع معلومات تتناسب مع كافة الفئات العمرية التي تستخدم مواقع التواصل الاجتماعي للحصول على المعلومات التي تحتاجها والأخذ بعين الاعتبار أن كل فئة عمرية تحتاج إلى معلومات محددة. ومع تقدم أعمار المستهلكين المتعاملين مع هذه المواقع يزداد بحثهم واهتمامهم بنوعية المعلومات التي يحصلون عليها من هذه المواقع. كما يجب العمل على تحسين نوعية المعلومات في سبيل كسب ثقة المستهلكين من خلال المصداقية في المعلومات التي تقدمها. This study aimed to defining the role of social communication sites in offering information to customers when doing buying where sites and nets of social communication became today a device which is available to different groups of society, and these sites were recognized it popularity and continuous contact with customers. So that companies found that these site are considered a good environment to get its agents through using it as a device for spreading its products, and this encouraged customers using these sites in order to get the available information through it and taking the suitable buying decision. And this study has been through distributing questioner convenience sample from ready- made clothes customers in the Syrian coast, and the number questioners was 84 questioner, by this they get the required data. Also, they used spss program the statics in analyzing data and getting the results. From these results which they get was that the most of social communication sites which are used in searching for information is Facebook site and the least is twitter. And the scientific level for consumers plays great part in searching for the information through the these sites. In addition to that they achieved the more the consumer becomes older the more his search for information he wishes and helps him in taking the suitable buying decision, so that it necessary to ask job companies for making use of all the available social communication sites for their customers in spreading their jobs and producing all information which customers need in addition to putting information suiting all age groups that use social communicate sites to get information you need by considering that all age groups need specific information. with increases age of consumers those using these sites they increase search and interest in kind of information which consumers to have it from this sites. And must be working for improving kind of information for getting trust of customers through the truthful information which produce.